KEWENANGAN JAKSA DALAM MELAKUKAN PENYIDIKAN TERHADAP TINDAK PIDANA KORUPSI - Horas Monang Jeffry Andi Gultom; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
Law enforcement against criminal acts of corruption is considered very serious, so it is necessary for the Prosecutor's Office to be able to deal with criminal acts of corruption in accordance with the laws and regulations in force in Indonesia, which form the basis for prosecutors in conducting investigations into corruption cases contained in Law No: 16 of 2004 concerning the Prosecutor's Office is regulated in Article 30 paragraph (1) letter d. Prosecutors have the authority to conduct investigations into certain criminal acts. Law enforcement in the investigation of corruption by the North Sumatra High Prosecutor's Office which has increased the professionalism of investigators is important, because a misapplication of the article will be fatal to the subsequent law enforcement process and the inability to apply normative criminal law rules to concrete legal legal events that occur will have an impact on the bluntness of law enforcement, and the obstacles faced by the Attorney General's Office in carrying out Corruption Investigations are firstly internal constraints and Second, external constraints. ,. The Process of Recovering State Financial Losses through civil law means in the form of a civil lawsuit against a person involved in a corruption case, and a civil lawsuit against the convict and/or his heirs if the decision has permanent legal force